2007
DOI: 10.1530/eje-07-0290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of extended human leukocyte antigen haplotype association with Addison's disease in three populations

Abstract: Objective: Addison's disease is an organ-specific autoimmune disorder with a polygenic background. The aim of the study was to identify non-class II human leukocyte antigen (HLA) susceptibility genes for Addison's disease. Design and methods: Addison's disease patients from three European populations were analysed for selected HLA-DR-DQ alleles and for 11 microsatellite markers covering w4 Mb over the HLA region. Subjects were 69 patients with Addison's disease from Estonia (24), Finland (14) and Russia (31). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 22 publications
4
11
0
2
Order By: Relevance
“…Using in silico typing from sequencing reads, we could confirm the risk conferred by certain HLA haplotype pairs [8,[67][68][69]. The strongest risk factor is by far the combination of HLA alleles DRB1*03:01 and DRB1*04:04, as previously shown in other populations [8,[67][68][69].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Using in silico typing from sequencing reads, we could confirm the risk conferred by certain HLA haplotype pairs [8,[67][68][69]. The strongest risk factor is by far the combination of HLA alleles DRB1*03:01 and DRB1*04:04, as previously shown in other populations [8,[67][68][69].…”
Section: Discussionsupporting
confidence: 67%
“…The strongest risk factor is by far the combination of HLA alleles DRB1*03:01 and DRB1*04:04, as previously shown in other populations [8,[67][68][69]. Despite the fact that we selected only patients with AAD reacting against the same autoantigen, 21-hydroxylase, we detect a great variability at the HLA locus.…”
Section: Discussionsupporting
confidence: 61%
“…In detail, the DRB1*11/ DQB1*0301 genotype is associated with that frequently found in aPOF (14); the DQA1*0501-DQB1*0301 haplotype and DRB1*04-DQ7-9 alleles are both reported as predisposing for UC (15). Several studies showed that the HLA DR3/4, DQ2/ DQ8 (DQA1*0501-DQB1*0201/ DQA1*0301-DQB1* 0302) is the highest-risk predisposing genotype to AD, and the haplotype DQB1*0302-DRB1*0404 is known to confer susceptibility to AD (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies of the adrenal tissue of deceased AD patients show a predominant mononuclear cell infiltrate [6,7]. IAD and APS2 are associated with certain HLA haplotypes or allelic combinations, in particular DR3-DQ2 and DR4-DQ8 [8,9] which are known to predispose to other T cell-mediated autoimmune diseases such as type 1 diabetes and celiac disease. Although less reported, association with the HLA A1-B8-DR3 ancestral haplotype has also been described in earlier studies [10,11].…”
Section: Introductionmentioning
confidence: 99%